2008
DOI: 10.1529/biophysj.108.139626
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Methodology for Defining Coarse-Grained Sites in Large Biomolecules

Abstract: Coarse-grained (CG) models of biomolecules have recently attracted considerable interest because they enable the simulation of complex biological systems on length-scales and timescales that are inaccessible for atomistic molecular dynamics simulation. A CG model is defined by a map that transforms an atomically detailed configuration into a CG configuration. For CG models of relatively small biomolecules or in cases that the CG and all-atom models have similar resolution, the construction of this map is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
246
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(248 citation statements)
references
References 51 publications
2
246
0
Order By: Relevance
“…These results reveal correlation between the dynamics of the DB loop region and the state of the bound nucleotide. This correlation is also consistent with a previous coarse-grained study that found the dynamics of the DB loop region in ATP monomeric actin to be distinct from the rest of the protein (40).…”
Section: Resultssupporting
confidence: 92%
“…These results reveal correlation between the dynamics of the DB loop region and the state of the bound nucleotide. This correlation is also consistent with a previous coarse-grained study that found the dynamics of the DB loop region in ATP monomeric actin to be distinct from the rest of the protein (40).…”
Section: Resultssupporting
confidence: 92%
“…Earlier choices for OP-like variables include principal component analysis (PCA) modes to identify collective behaviors in macromolecular systems, [13][14][15] dihedral angles, 16,17 curvilinear coordinates to characterize macromolecular folding and coiling, 18 bead models wherein a peptide or nucleotide is represented by a bead which interacts with others via a phenomenological force, and spatial coarse-grained models. [19][20][21] These approaches suffer from one or more of the following difficulties: (1) characteristic variables are not slowly varying in time; (2) macromolecular twist is not readily accounted for; (3) their internal dynamics, and hence inelasticity of their collisions is neglected; and (4) the forces involved must be calibrated for most new applications. In contrast as discussed in Secs.…”
Section: Introductionmentioning
confidence: 99%
“…For big systems, this becomes computationally expensive. 21 Improvements to EDS have been made via a technique called amplified collective motion. However normal modes derived from this model via an anisotropic network 13 may not be consistent with all-atom models, especially if the structure undergoes severe deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors show that, in protein association, their model provides a good approximation of the all-atom potential, if the distance between the protein surfaces is larger than the diameter of a solvent molecule. In a recent work, Zhang et al 8 proposed a method to define CGs that reflect the collective motions computed by a principal component analysis of an atomistic MD trajectory. Each CG site is the com of a domain, i.e., a group of contiguous CR atoms that move in a highly correlated fashion.…”
Section: Introductionmentioning
confidence: 99%